2018
DOI: 10.24237/djps.1402.383b
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between SVM and K-NN for classification of Plant Diseases

Abstract: Vegetable crops differ in size, shape, and color and which its suffer from this many leaf batches according to a particular reason. As a result of the plant, pathogens happen for Leaf batches. In agriculture whole fructification, it is essential to learn the origin of plant disease bundles early

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Using the permissions dataset, we assessed the various classifiers-Random Forest, SVM, Naïve Bayes, and Rotation Forest. [27], [28] Although the field of research on using intelligent algorithms to detect ransomware is still in its early stages, it is expanding, suggesting that there may be opportunities for future advancements in this area. There are still untapped possibilities for future advancements in machine learning algorithms for ransomware detection.…”
Section: Dataset Names Behavioral Features Machine Learning Deep Lear...mentioning
confidence: 99%
“…Using the permissions dataset, we assessed the various classifiers-Random Forest, SVM, Naïve Bayes, and Rotation Forest. [27], [28] Although the field of research on using intelligent algorithms to detect ransomware is still in its early stages, it is expanding, suggesting that there may be opportunities for future advancements in this area. There are still untapped possibilities for future advancements in machine learning algorithms for ransomware detection.…”
Section: Dataset Names Behavioral Features Machine Learning Deep Lear...mentioning
confidence: 99%
“…x is the input vector while K is the kernel function to operates on two vectors. b is the scalar value [25].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…There are no predefined statistical methods to find the most favorable value of K. However, some researchers e.g. [36,37], found that k = 1 is the optimal value when performing a categorization task, because when k = 1, the KNN algorithm classifies the object to its nearest neighbor. In this article, and after many tests, we found that k = 1 gives the best recognition rate, so we decided to use this value in all our experiments.…”
Section: Choice Of "K"mentioning
confidence: 99%